Effect of Traditionally Used Neem and Babool Chewing Stick (Datun) on Streptococcus Mutans: An In–Vitro Study - ABHISHEK SHARMA; BHARAT SANKHLA; SUJAL M PARKAR; SUDHEER HONGAL; THANVEER K; AJITHKRISHNAN CG (Journal of Clinical and Diagnostic Research, 2014)
Purpose: There are various plants, which are used as chewing sticks in different parts of the world. Several studies have been reported on the antimicrobial effects of chewing sticks on oral bacteria. This study was conducted to evaluate the effectiveness of traditionally used neem and babool chewing sticks (datun) extracts on Streptococcus mutans. Materials and Methods: The present invitro study was conducted to assess effectiveness of 5%, 10%, and 50% neem and babool extract on Streptococcus mutans. The ditch plate method was used to test the antimicrobial activity. Ditches were prepared on blood agar plates with the help of punch having 6mm diameter. The plates were left for 1h at room temperature and then incubated at 37°C for 48h and examined for zone of inhibition. Results: There was no zone of inhibition observed with 5% babool and neem aqueous extract. There was significant difference in mean diameter of zone of inhibition of 10% neem and babool extract (p-value 0.001 < 0.05). Similarly the mean difference in 50% neem and babool extract was found to be significant (p-value < 0.001). Conclusion: Both neem and babool extracts had antimicrobial activity against Streptococcus mutans, while antimicrobial activity was significantly higher in neem aqueous extract than babool aqueous extract.